Pelatihan Pembukuan Sederhana untuk Meningkatkan Literasi Keuangan pada UMKM di Desa Penujak Kecamatan Praya Barat - Wardiningsih, Reny; Wahyuningsih, Baiq Yuni; Sugianto, Riris (Lembaga Yasin AlSys, 2022)
Small, Micro and Medium Enterprises (MSMEs) are one of the main pillars of the national economy that have an independent perspective and have great potential to improve people's welfare. MSMEs are one of the businesses that can survive in deteriorating economic conditions, especially during the Covid-19 pandemic. Therefore, MSMEs should have good financial management so that the business they run can be sustainable. MSMEs in Penujak Village, West Praya Regency, have not kept books of account. Most of these business actors do not separate personal and business assets, in determining the selling price based on insting. The purpose of the Community Service Implementation activities in simple bookkeeping training for MSMEs is to be able to independently compile simple books or records related to expenses, income, costs and profits earned and to know the progress of their business. The method of implementing community service in Penujak Village is divided into three stages, namely the initial stage of observation and preparation, the second stage is the implementation of training, and the final stage is mentoring as well as monitoring. The results obtained from this activity are being able to increase knowledge and skills in running their business through simple bookkeeping/recording that is easy to apply to achieve a sustainable business.